INFORMATIONAL CONFRONTATION BETWEEN THE RUSSIAN FEDERATION AND THE USA DURING THE “TULIP REVOLUTION” IN KYRGYZSTAN - Lina Yuryevna Medovkina (Science and Innovation Center Publishing House, 2017)
In the present article the author considers the problem of informational confrontation between the Russian Federation and the USA during the “Tulip Revolution” of 2005 in Kyrgyzstan. Kyrgyzstan became the first post-socialist country in Central Asia where there had been a color revolution. It is noted that in 2004 the US State Department awarded grants to non-governmental organizations of Kyrgyzstan as help for the independent media and for dissemination of propaganda information. Financial and human resources provided by the United States gave the united Kyrgyz opposition enough financial and moral support to have the opportunity to go on the offensive on Russia in the information field. The confrontation in the information field of the Russian Federation and the United States during the “Tulip Revolution” was won by the West and lost by Russia, as their technology of counteraction to information influence were weak.